2006
DOI: 10.1002/marc.200600451
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(tartar amides) as Bio‐Inspired Antifreeze Additives

Abstract: Summary: Multifunctional poly(tartar amides) have been synthesized and used as bio‐inspired antifreeze additives. It is shown that these polymers strongly interfere with the crystallization process of water in comparison to commercially available commodity polymers. While the addition of the poly(tartar amides) results in minor freezing point depression, as is shown by differential scanning calorimetry, a strong change in the ice crystal morphology is evident. Wide‐angle X‐ray scattering and optical microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 17 publications
1
27
1
Order By: Relevance
“…Although this observation was deduced to signal a change in ice crystal morphology, it may also reflect preferred orientations of the ice crystals such that the (002) planes are not parallel to the sample stage. In a related investigation, the (002) peak was absent for ice crystals grown in the presence of a poly(tartar amide) with glycol side chains, and the (101) intensity was substantially reduced (27). This study also revealed that the (002) reflection was negligible when ice crystals were grown in the presence of poly(ethylene glycol), specifically PEG-6 (average M n = 5,900).…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…Although this observation was deduced to signal a change in ice crystal morphology, it may also reflect preferred orientations of the ice crystals such that the (002) planes are not parallel to the sample stage. In a related investigation, the (002) peak was absent for ice crystals grown in the presence of a poly(tartar amide) with glycol side chains, and the (101) intensity was substantially reduced (27). This study also revealed that the (002) reflection was negligible when ice crystals were grown in the presence of poly(ethylene glycol), specifically PEG-6 (average M n = 5,900).…”
Section: Resultsmentioning
confidence: 57%
“…This study also revealed that the (002) reflection was negligible when ice crystals were grown in the presence of poly(ethylene glycol), specifically PEG-6 (average M n = 5,900). This study was attributed to an earlier postulate that macromolecules can block the c-directional growth of ice crystals (51), producing ice nanoplatelets interleaved with polymers such that the diffraction intensity would be diminished (27). Whereas ) at −1.0 ± 0.1°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also shown that hyper-branched polyglycidol influences of the crystallization kinetics of ice (slowing down) and leads to changes in the ice crystal morphology. Recently Yagci et al 177 showed that multifunctional poly (tartar amides) polymers can strongly interfere with the crystallization process of water in comparison with commercially available commodity polymers. While the addition of the poly(tartar amides) results in a minor freezing point depression, as is shown by differential scanning calorimetry, a strong change in the ice crystal morphology is evident.…”
Section: Mimicking Afp and Afgp Behavior For Antifreeze Applicationsmentioning
confidence: 99%